Effect of Temperature and Pressure on Structural and Magnetic Properties of Strontium-Filled Skutterudites SrT4Sb12: LDA and LSDA Calculations - Amari, Malika; Ameri, Mohammed; Bouyakoub, Amel Zahira; Arbouche, Omar; Bidai, Kada; Bensaid, Djillali; Ameri, Ibrahim; Al-Douri, Yarub (Springer Verlag, 2018)
The structural, elastic, thermodynamic, magnetic, and electronic properties of strontium-filled skutterudite component SrFe4 Sb12 using the full potential-linear muffin-tin orbital (FP-LMTO) calculation were studied. The local density approximation (LDA) and local spin density approximation (LSDA) for predicting the physical properties were used. The internal parameters used to calculate the ground state properties such as lattice constant, bulk modulus, and its derivative pressure were optimized. Then, we have deduced the elastic constants, shear modulus G, Young modulus E, Poisson’s ratio ν, anisotropic parameter A, ratio B/G, and the Debye temperature (θD). The quasi-harmonic Debye model as implemented in the Gibbs program is applied to determine the thermal properties such as the Debye temperature (θD), heat capacity Cv and Cp, thermal expansion coefficient α Helmholtz free energy (A), Gibbs free energy (G), entropy (S) and internal energy (U) at different pressures and temperatures.